Solve the following linear differential equations
1) dy/dx + 2y = sinx
2) dy/dx + y = e^x
3) dy/dx +(4/x)y = x³y³
1) "\\frac{dy}{dx}+2y=\\sin \\left(x\\right)" - First order linear Ordinary Differential Equation
A first order linear ODE has the form of "y'\\left(x\\right)+p\\left(x\\right)y=q\\left(x\\right)"
Substitute "\\frac{dy}{dx}\\mathrm{\\:with\\:}y'\\:"
"y'\\:+2y=\\sin \\left(x\\right)"
The equation is in the first order linear ODE form
We find the integration factor: "\\mu(x) = e^{2x}"
We put the equation in the form "(\\mu(x)y)' = \\mu(x)q(x):" "(e^{2x}y)' = sin(x)e^{2x}"
Solve "(e^{2x}y)' = sin(x)e^{2x} :" "y=-\\frac{\\cos \\left(x\\right)}{5}+\\frac{2\\sin \\left(x\\right)}{5}+\\frac{c_1}{e^{2x}}"
Answer: "y=\\large-\\frac{\\cos \\left(x\\right)}{5}+\\frac{2\\sin \\left(x\\right)}{5}+\\frac{c_1}{e^{2x}}"
2) "\\frac{dy}{dx}+y=e^x" - First order linear Ordinary Differential Equation
A first order linear ODE has the form of "y'\\left(x\\right)+p\\left(x\\right)y=q\\left(x\\right)"
Substitute "\\frac{dy}{dx}\\mathrm{\\:with\\:}y'\\:"
"\\frac{dy}{dx}+y=e^x"
The equation is in the first order linear ODE form
We find the integration factor: "\\mu(x) = e^{2x}"
We put the equation in the form "(\\mu(x)y)' = \\mu(x)q(x):" "(e^xy)'=e^{2x}"
Solve "(e^xy)'=e^{2x}:" "y=\\frac{e^x}{2}+\\frac{c_1}{e^x}"
Answer: "y=\\large\\frac{e^x}{2}+\\frac{c_1}{e^x}"
3) "\\frac{dy}{dx}+\\left(\\frac{4}{x}\\right)y=x^3y^3" - First order Bernoulli Ordinary Differential Equation
A first order Bernoulli ODE has the form of "y'+p\\left(x\\right)y=q\\left(x\\right)y^n"
Substitute "\\frac{dy}{dx}\\mathrm{\\:with\\:}y'\\:"
"y' + \\left(\\frac{4}{x}\\right)y=x^3y^3"
The equation is in first order Bernoulli ODE form
The general solution is obtained by substituting "\\nu = y^{1-n}" and solving "\\frac{1}{1-n}\\nu' + p(x)\\nu=q(x)"
Transform to "\\frac{1}{1-n}\\nu' + p(x)\\nu=q(x)" : "\\large-\\frac{\\nu'}{2}+\\frac{4\\nu}{x}=x^3"
Solve "\\large-\\frac{\\nu'}{2}+\\frac{4\\nu}{x}=x^3" : "\\nu = \\large\\frac{x^4}{2}+c_1x^8"
Substitute back "\\nu = y^{-2}:" "y^{-2} = \\large\\frac{x^4}{2}+c_1x^8"
Isolate y: "\\large y=\\sqrt{\\frac{2}{x^4\\left(1+2c_1x^4\\right)}},\\:y=-\\sqrt{\\frac{2}{x^4\\left(1+2c_1x^4\\right)}}"
Answer: "\\large y=\\sqrt{\\frac{2}{x^4\\left(1+2c_1x^4\\right)}},\\:y=-\\sqrt{\\frac{2}{x^4\\left(1+2c_1x^4\\right)}}"
Comments
Leave a comment